SCAFFOLDING AS USED IN THE WRITING PROCESS OF AN ENGLISH WRITING COURSE - Sulindra, Eric (Akademi Sekretari Widya Mandala, 2018)
Dealing with writing, there are two major problems for the students in English courses. The first is in finding ‘what to write’ (generating ideas about a specific topic) and the second is how to develop the idea that has been invented. Developing the ideas includes using the appropriate grammar and sentence structure in each paragraph and also developing paragraphs to form a composition. The paper overviews how scaffolding technique is able to help students in English classes to learn writing. Scaffolding is regarded as suitable for teaching writing because of the approach used in the technique focuses more to the approach rather than to the product. A general description and overview of how students are supported by scaffolding technique in generating ideas related to a particular topic and producing an appropriate text organization, is presented here.